A novel MTPA theory based bottom‐up approach towards parametric and structural design of interior PMSM for electric vehicles. (22nd November 2017) - Iyer, Lakshmi Varaha; Lai, Chunyan; Dhulipati, Himavarsha; Mukundan, Shruthi; Mukherjee, Kaushik; Tjong, Jimi; Kar, Narayan C.
Summary: Understanding the merits of using an interior permanent magnet synchronous machine (IPMSM) for propulsion in all‐electric vehicles and challenges in conventional electric machine design approach, this paper proposes a novel model based design approach for three‐phase IPMSMs. Firstly, a novel bottom‐up IPMSM design methodology involving closed‐form analytical equations and per unitization approach based on maximum‐torque‐per‐ampere control theory is proposed. Using this approach, preliminary parametric and structural design of the machine with (1) a desired constant torque region; (2) desired reluctance torque percentage; (3) a specific constant power region; and (4) optimal angle of the stator current vector can be obtained. Thereafter, the proposed model based design approach has been verified through finite element analysis conducted on the electromagnetic model of a downscaled electric vehicle (EV) motor designed. Finally, the designed machine has been prototyped and experimentally tested for designed parameters and output performance with maximum‐torque‐per‐ampere and vector control strategies.